Vallejo and the ghostly dismantling of the Nation: the National Anthem in Escalas’ «Liberación» - de Lima, Paolo (2023)
This article analyses the short story «Liberación» by César Vallejo, included in the book Escalas (1923), based on an interpretation of its central anecdote (the story of a prisoner who pays the price of imprisonment as a result of a swindle by a member of high society) and the inclusion of the playing of the Peruvian National Anthem in the space of the Panopticon as a symbolic framework for this anecdote, as a questioning of the sense of nation as a system of social equality. At the same time, emphasis is placed on the fact that the use of fantastic elements (the ghostly appearance of the prisoner in the final line of the story) is a resource used by Vallejo to reflect on the ambiguous condition of patriotic symbols, which turns out to be an effective means of highlighting their illusory nature. The lurking ghost of injustice and oppression would be a sort of «real» presence that swarms behind the fiction of reality (the representation of the «Peruvian individual» and of Peru contained in the hymn).